2019
DOI: 10.29333/iejme/5885
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Science, Technology, Engineering and Mathematics (STEM) Program on Students’ Achievement in Mathematics: A Meta-Analysis

Abstract: The positive impact of Science, Technology, Engineering, and Mathematics (STEM) programs on student achievement, attitude, interest, communication skills and problem-solving has alerted the education community to reform instructional approaches in STEM subjects. This meta-analysis study aims to analyze previous studies' results of STEM program impacting students' mathematics achievement. The criteria for inclusion of literature in the meta-analysis were: published between 1998 and 2017, employed experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…According to Cohen et al's (2007, p. 521) effect size classification, this result means that STEM education had a strong effect on the academic achievement levels of students. In addition, when these results were compared with the results of the study conducted by Saraç (2018), an effect size larger than three times was found. While the effect size of 44 studies in the present study was positive, only 1 study was found to have negative effect.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…According to Cohen et al's (2007, p. 521) effect size classification, this result means that STEM education had a strong effect on the academic achievement levels of students. In addition, when these results were compared with the results of the study conducted by Saraç (2018), an effect size larger than three times was found. While the effect size of 44 studies in the present study was positive, only 1 study was found to have negative effect.…”
Section: Discussionmentioning
confidence: 83%
“…As a result of the analyses, we found that the studies had a heterogeneous distribution and according to this result, we decided to use the REM model. When it is considered that a total of 11 studies were reached about STEM education in Turkey in a study conducted by Saraç (2018), we found that there has been a serious increase in the number of studies since 2018. Kalemkuş (2019) also stated that studies about STEM began to intensify in 2018.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In today's world, there is a need for individuals with 21st-century skills such as critical thinking, entrepreneurship, communication, collaboration, decision-making, leadership, problem-solving, responsibility, and creativity. One of the educational approaches in which these individuals are nourished is the STEM approach (Ergün & Külekci, 2019;Siregar et al, 2019). STEM was first mentioned by The National Science Foundation director J.…”
Section: Introductionmentioning
confidence: 99%